Two new pathotypes 125R28 and 93R37 of Puccinia triticina on wheat from India and sources of resistance - BHARDWAJ*, S.C.; PRASHAR, M.; KUMAR, SUBODH; JAIN, S.K.; SHARMA, Y.P.; KALAPPANAVAR, I.K. (Indian Phytopathology, 2011)
Two new pathotypes of Puccinia triticina designated as 125R28 and 93R37 are described. Pathotype125R28 hasÂ spread to Maharashtra, Madhya Pradesh and Gujarat and was observed in 8 per cent of the samples of this year whereas otherÂ pathotype was identified in two samples only. Most of the present day pathotypes have virulence for Lr26 but pathotypeÂ 125R28 is avirulent. Both the pathotypes have evolved with one step change in the existing pathotypes. Avirulence/virulenceÂ structure and rust resistance sources are listed.